Special Issue Preface - Khadem, Mohammad Miftaur Rahman Khan (International Journal of Industrial Engineering: Theory, Applications and Practice, 2012)
The Industrial Engineering and Operations Management (IEOM) Forum organized the 2nd International Conference on Industrial Engineering and Operations Management (IEOM 2011) which was held from January 22-24, 2011 in Kuala Lumpur, Malaysia. The conference aimed to provide a forum for academics, researchers and practitioners to exchange ideas and recent developments in the field of Industrial Engineering and Operations Management. The conference was also expected to foster networking, collaboration and joint effort among the conference participants to advance the theory and practice as well as to identify major trends in Industrial Engineering and Operations Management. The conference goals were successfully achieved with participation of 200 members representing more than 40 countries around the world. From about 200 good quality papers presented in the conference, eight papers were selected to be considered for publication in the IJIETAP as a special issue after further review. Six of the eight papers have been selected for final publication. We congratulate the authors whose papers appear in this special issue. The papers represent production systems design, facilities layout design and product design, all important topical areas in industrial engineering. I would like to thank the editor-in-chief Dr. Arunkumar Pennathur, and other members of the IJIETAP for their support in organizing this special issue from the IEOM conference.